Estetyka pewnego internetowego tekstu podręcznikowego = Aesthetics of Internet textbooks - Boniecka, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author, reading the internet manual on social knowledge, noticed many language errors, especially syntax, punctuation, inflexion, spelling, lexical. She also noticed inability to edit the text, including Lack of uniformity in the use of paragraphs, lines, adjustments, etc.
Keywords: estetyka; podręcznik; skrypt; redakcja tekstu; aesthetics; textbook; script; text editing